Цифровая грамотность как средство от инфодемии Covid-19 в Индонезии (Digital Literacy as an Antidote to Covid-19 Infodemic in Indonesia) - Hoesin, Cut Fitri Indah Sari; Poplavskaya, Natalia V.; Hossain, Barek (Jurnal Cita Hukum, 2022)
Since the beginning of the pandemic, incorrect information or fake news related to Covid-19 spread out uncontrollably and caused panic and unrest in the community. This is in line with the report from the Ministry of Communication and Information of the Republic Indonesia that as of February 2022, there are 2121 fake news related to COVID-19 or the infodemic circulated in social media in Indonesia. For this reason, the need for the role of digital literacy in preventing and anticipating infodemic is discussed in this paper. Using a qualitative research approach with library research methods, it was found that the need of digital literacy to raise awareness of selecting and checking the sources of information, training critical thinking to every information, the importance of developing skills to identify incorrect information, and correcting infodemic in the society.